Moringa oleifera Leaves Possible Uses as Environmentally Friendly Material: A Review - Ali, Eman N. (International Scientific Academy of Engineering & Technology (ISAET), 2014)
New uses of Moringa oleifera leaves have been found by many researchers for the last two decades which introduced new material in pharmaceutical and water treatment industry. Moringa oleifera leaves can be used as a medicine for many diseases, as antibacterial, antioxidant, anticancer. In addition it can be used as a protein supplement for human being and animals due to high protein content. Moringa oleifera leaves are unique because of their tremendous amounts of minerals but lower amounts of harmful compounds and it can be considered as safe supplement because besides that it is not toxic. In addition, it was found that it can work as a biosorbent for heavy metals in water treatment. Therefore, it can be considered as a natural product and environmentally friendly material.